Konsepsi dan Hak Asasi Manusia Atas Lingkungan Hidup yang Sehat dan Baik - Ahmad Arif Fadilah; Muhammad Rohim; Hayla Erian; Shilla Safitri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Environmental human rights violations have occurred in almost all levels of society. These violations are considered to threaten Indonesian human civilization. In turn, the violated economic, social, and cultural rights, as well as civil and political rights, will be fulfilled and resolved. Human rights to a good, healthy, and balanced environment have not been implemented in environmental management in Indonesia. In relation to the problem of environmental damage, it is important to study human rights from a human rights perspective. The aim is to explain the definition of human rights and environmental rights, how human rights are regulated in Indonesian law and how human rights are considered as rights to a good and healthy environment. The results of the study explain two things. First, humans are part of the ecosystem, where they have a strong relationship with their environment. Given to them by God as humans, the right to a healthy environment is a basic human right. Second, the right to a good and healthy environment has become a norm throughout the world and in the region. Third, although there have been resolutions, covenants, and regulations of the Universal Declaration of Human Rights at the national level, the right to a good and healthy environment is still poorly respected at both the global and national levels. Developed countries contribute significantly to global warming, climate change, and environmental degradation globally, and they also make significant contributions nationally.